HUBUNGAN KUALITAS TIDUR DENGAN FUNGSI KOGNITIF PADA MAHASISWA FAKULTAS KEDOKTERAN UNIVERSITAS SUMATERA UTARA - Melly Leman; Lokot Donna Lubis; Milahayati Daulay; Cut Adeya Adella; Eka Roina Megawati (BAPIN-ISMKI (Badan Analisis Pengembangan Ilmiah Nasional - Ikatan Senat Mahasiswa Kedokteran Indonesia), 2021)
ABSTRACT Background: Sleep is an essential need in daily lives with abundant functions, especially neuron restoring process in neocortex after various activities. Poor sleep quality is often found, resulting from the needs of work, education, lifestyle, and sociocultural demand. It could hinder cognitive function thus affecting daily life quality. Thus, the objective of this study is to assess the risk factors of poor sleep quality and its relation to cognitive function of college students at Faculty of Medicine, Universitas Sumatera Utara. Method: This research uses an analytic method with cross-sectional design where the collection of data is simultaneously taken at one time. The data are primarily obtained from interviews utilising validated questionnaires, Pittsburgh Sleep Quality Index (PSQI) for sleep quality and Montreal Cognitive Assessment (MoCA) for cognitive function, with stratified random sampling technique. Results: The incidence of poor sleep quality of the samples is 69% with the predominance of being male, aged 17-19, having higher body mass index, and consuming caffeinated beverages. Meanwhile, the incidence of mild cognitive impairment is 42%. The Chi-Square and Spearman Rank tests show a significant relation (p=0.009) and weak correlation (r=0.262, p=0.008) between age groups and sleep quality, whereas there is no association of gender (p=0.517) and body mass index (p=0.322) with sleep quality. The Fisher’s Exact test yields no relation between consumption of caffeine (p=0.778) and sleep quality. According to the Chi-Square test, sleep quality is not associated with cognitive function as well (p=0.993). Conclusion. There is no association of sleep quality with cognitive function, however there is a significant relation and weak correlation between age groups and sleep quality.